RECEPTION COMPARISON ON PHYSIOGNOMY SCIENCE PIRASAT TOWARDS PIRASAT CHAPTERS OF SERAT TAJUSSALATIN AND FIRASAT CHAPTER OF TAJ AS SALATIN - Afandi, Haekal Rheza; Setyani, Turita Indah (International Review of Humanities Studies, 2023)
Pirasat (hereinafter referred to as PR) is a Javanese manuscript derived from Taj As Salatin (hereinafter referred to as TAS). A sentence was discovered at the beginning of the PR text that informs the manuscript was produced by scriber after hearing TAS text. PR research aims to reveal the path of PR derivation from TAS as an attempt to add on knowledge related to the history of the text. The method used in PR research is comparative literature to review the receptions that emerge from the manuscript that has been done philologically. Derivation of PR is showing that the text was translated directly from TAS, not through an adapted TAS text that was known in Javanese literature, called Serat Tajussalatin (hereinafter referred to as ST). PR has different characteristics that even though it is a translated text, it has been found that PR has different variations of eye physiognomy section, this made PR that had the most variative eye section compared to TAS and ST. PR is a Javanese manuscript from TAS which only contains the 19th chapter of the text, although PR is translated from TAS, PR shows the creativity of the author which is shown by how different section that has been obtained from TAS was added. This is evidence of the response that has been given by the scriber who has heard the text.